The interaction between jets and clouds in the 3CR galaxies - Hägele, G. F. (2008)
From the HST/WFPC2 3CR Snapshot Survey, data taken with the filter F555W, F702W and narrow-ramp, a set of galaxies with noticeable extended structure were selected (e.g. 3C 79, 3C 135, 3C 234, etc). All of these objects show large regions of [OIII] λ 5007˚A emission (narrow ramp filter) and the broad-band filters data show similar structures indicating the presence of strong emission in several lines over these regions. The morphology observed seems to be related (e.g. same position angle, direct overlapping or similar shape) with the radio-jet. For some candidates with these properties GMOS/Gemini spectroscopy was taken. These data (both HST direct imaging and Gemini spectroscopy) can be tested with diagnostic diagrams and total UV photons budget to understand the source of energy that is ionizing the gas. This source of ionization was commonly believed to be the UV photons emitted by the powerful active galactic nuclei (AGN), but several of these objects show clearly that shocks produced by the radio jet are the main cause of the observed gas line emission. We show in this work, the results obtained over some of these radio-galaxies: 3C 135, 3C 180, 3C 234 and 3C 284.